The Future Strategy of the Professional Sports Clubs Case Study: Sepahan Club - Rasool Nazari; Zahra Sohrabi; Mehrdad Moharamzadeh (Sports Business Journal, 2022)
Purpose: The purpose of the present study was to determine the strategic future of the Sepahan sports club.Methodology: In the present study, cross-effects analysis was used as one of the foresight methods. A combination of qualitative and quantitative methods, including interviews and checklists, was used to collect data. The research was from interpretive philosophy, inductive approach; case study strategy; qualitative method; single-point time horizon; research contributors, strategists, experts in foresight, prominent managers, and the club's experts. Thirty individuals were selected through purposive sampling using the snowball method. The research tools were semi-structured and exploratory interviews. Data were analyzed using the Micmac and scenario wizard software.Finding: The most important strategic factors include supporting public and private bodies, enhancing cultural and social responsibility, developing media awareness, managing systems and processes, developing appropriate infrastructure, improving financial and environmental impacts, and security was identified as being consistent with the club's sustainable development. Finally, two scenarios include scenario consisting of financial resources allocation, unit, and integrated management components; and the second is one the components of specialization and highlighting and modeling to chart the club's future.Originality: In this study, the strategic plan has used both the quantitative and qualitative methods.